Correlation between Serum Platelet Count and Cognitive Function in Patients with Atrial Fibrillation: A Cross-Sectional Study. (22nd March 2021) - Sun, Dandan; Wang, Quanliang; Kang, Jie; Zhou, Jie; Qian, Ruijuan; Wang, Wenqing; Wang, Haichen; Zhang, Qingyun
Abstract : Background . The risk of cognitive impairment in patients with atrial fibrillation is significantly increased. Its occurrence may be related to blood hypercoagulable state and immune inflammatory reaction. Platelets can mediate immune inflammatory response, but there is no evidence about the relationship between platelet count and cognitive function in patients with atrial fibrillation. Purpose . To explore whether there is a certain correlation between platelet count and cognitive function in patients with atrial fibrillation. Methods . A cross-sectional study was conducted in a single center in China, including 254 patients with atrial fibrillation. Cognitive function assessment and clinical and laboratory examinations were performed on all participants. After adjusting the related confounding factors, the relationship between platelet count and cognitive function was analyzed. Results . A total of 254 subjects with an average age of 59.71 ± 11.14 years were included. The average platelet count was 208.15 ± 68.30, and the average score of cognitive function was 19.29 ± 6.78. Result of fully adjusted binary logistic regression showed platelet count was negatively associated with the cognitive function score after adjusting confounders (hazard ratio (HR) = 0.000, 95%CI −0.01, 0.01). A nonlinear relationship was detected between platelet count and the cognitive function score, whose point was 230. The effect sizes and the confidence intervals of the left and right sides of the inflection point were 0.03 (0.01–0.05, P for nonlinearity = 0.011) and −0.03 (−0.05–0.00, P for nonlinearity = 0.023), respectively. Conclusion . Platelets have a nonlinear relationship with cognitive function in patients with atrial fibrillation. This finding suggests that, in patients with atrial fibrillation, platelets should be maintained at about 230.